PENGARUH UKURAN DEWAN KOMISARIS, DIREKSI, KOMISARIS INDEPENDEN, STRUKTUR KEPEMILIKAN, DAN INDEKS CORPORATE GOVERNANCE TERHADAP ASIMETRI INFORMASI - Arko Soni Raharjo; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of size  board of commisioner, board of director, independent commisioner, ownership structure, and corporate governance index to asymmetric information listed in Indonesia Stock Exchange 2008-2012. In this study, there are six independent variables; size of board  commissioner, proportion of independent commissioner, size of board director, institutional ownership, managerial ownership, Corporate Governance Perception Index, and one dependent variable is asymmetric information.The sampling mehod used in this research is purposive sampling method. Type of regression model used in this study is multple regressions. The total final sample used were 77 companies.The results of Statitical test show that (Test F) all independent variables affect asymmetric information collectively. The influential of independent variable Corporate Governance Perception Index and proportion of independent commissioner on the T test is negative significantly. While institutional ownership, board of commissioner and director size does not affect asymmetric information and managerial ownership is pointing to the positive direction.